Analysis of the Implementation of the Maritime Labour Convention (MLC) 2006 as an International Regime Toward Indonesian Seafarers in South Korea - Higia Hendriyati; M. Rafa Akhdan Naufal; Ryan Nailur Raja (Ilomata International Journal of Social Science, 2026)
This study examines the implementation of the Maritime Labour Convention (MLC) 2006 as an international regime in the context of Indonesian seafarers working in South Korea. Using an international regime perspective that emphasizes norms as instruments governing the behavior of member states, this research contributes novelty by revealing operational differences between the internationally navigating fish carrier sector and the small-scale fishing vessel sector. Employing a descriptive qualitative method, primary data were obtained through in-depth interviews with key informants namely a marine engineer officer on a merchant vessel and an official of the Jangkar Karat Indonesia labor union selected through purposive sampling based on work experience, and further strengthened by thematic analysis of complaint records from BP2MI. The findings indicate that large merchant vessels tend to demonstrate compliance with MLC 2006 standards, while small fishing vessels still exhibit significant violations, including working hour violations, wage discrepancies, and inadequate health protection for seafarers. This study concludes that ratification status does not automatically guarantee comprehensive compliance, and that strengthening oversight mechanisms and transnational cooperation particularly between Indonesia and South Korea is essential to closing this implementation gap.